2007
DOI: 10.1016/j.diabres.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Collagen I (GC) impairs angiogenesis in vitro—A study using an innovative chamber for cell research

Abstract: Studies of cell-matrix, cell-cell interaction, or angiogenesis on different matrices require simultaneous comparison of read-out parameters from differently treated companion cells. The culture conditions (cell number, temperature, volume of culture medium) in different chambers are not completely equalized using conventional methods. It has been reported that cells growing in different environmental conditions may exhibit different proliferation patterns (2). Herein we describe an innovative chamber which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Interestingly, structurally altered collagen resulting from glycation may impact some of the steps in the angiogenic cascade. In this regard, glycated collagen type‐I inhibited endothelial cell cord formation in vitro as compared to non‐glycated collagen (Brodsky et al, 2006). To this end, studies have suggested that glycation near integrin binding RGD sites can impair integrin recognition thus potentially disrupting integrin signaling (Sakata et al, 2000).…”
Section: Cryptic Collagen Elements Within the Non‐cellular Tumor Micrmentioning
confidence: 99%
“…Interestingly, structurally altered collagen resulting from glycation may impact some of the steps in the angiogenic cascade. In this regard, glycated collagen type‐I inhibited endothelial cell cord formation in vitro as compared to non‐glycated collagen (Brodsky et al, 2006). To this end, studies have suggested that glycation near integrin binding RGD sites can impair integrin recognition thus potentially disrupting integrin signaling (Sakata et al, 2000).…”
Section: Cryptic Collagen Elements Within the Non‐cellular Tumor Micrmentioning
confidence: 99%